Comparing the Severity of Obsessive-Compulsive Symptoms in Pre-pregnancy, Pregnancy, and Postpartum Period among Women of reproductive age - Fatemeh Rajab Dizavandi; Azam Salar Haji; Masoumeh Kordi; Nastaran Vaghei; Saeed Vaghee (Mashhad University of Medical Sciences, 2019)
Background & aim: Obsessive-Compulsive disorder is considered as one of the most common disorders in pregnancy and postpartum period. There are few studies in this regard in Iran. Therefore, the purpose of the current study was to compare the severity of obsessive-compulsive symptoms in pre-pregnancy, pregnancy, and postpartum period among women of reproductive age. Methods: This descriptive-comparative study was carried out on 900 eligible women (500 non-pregnant women, 200 pregnant women, and 200 in postpartum period) referred to health centers in Mashhad in 2011, who were selected using multi-stage sampling method. The data were collected by Madezly and Yale Brown Obsessive-Compulsive scale and analyzed using descriptive statistics, Kruskal-Wallis one-way analysis of variance, and Mann-Whitney U test in SPSS software (version 11) with the confidence level of 95%. Results: The obtained results of Kruskal-Wallis test showed that there was significant statistical difference between the groups of pre-marriage (15.9±7.1), pregnancy (20.6±4.5), and postpartum period (20.9±5.1) in terms of mean score of obsessive-compulsive symptoms (P=0.007). Conclusion: Women in their pregnancy and postpartum period are at risk of obsessive-compulsive disorder that mostly are not recognized. As a Consequence, it is necessary for healthcare centers to take required measures in this regard.